Empowering leadership: District trainings in groundwater management under CGIAR’s National Policies and Strategies in Madhya Pradesh and Rajasthan - CGIAR (CGIAR, 2024)
Under the CGIAR Initiative on National Policies and Strategies, IWMI India, along with on-ground partners Centre for MicroFinance (CmF) and Professional Assistance For Development Action (PRADAN) conducted six district-level trainings on leadership development in participatory groundwater management in Madya Pradesh and Rajasthan states. These 2-day leadership development programs aimed to supplement the training and capacity-building efforts of the Atal Bhujal Yojna (ABY) – a participatory groundwater management scheme by the Govt of India.